Auditor’s Reputation, Auditor’s Industry Specialization and Audit Report Lag: Testing the Role of Audit Committee as Moderating Variable (Empirical Study on Manufacturing Companies Listed on the IDX in 2019 and 2020) - Jihan Afifah; Anis Chariri (Diponegoro Journal of Accounting, 2023)
The purpose of this research is to examine the influence of auditor reputation and auditor industry specialization on audit report lag, using the audit committee as a moderating variable. The dependent variable in this study is audit report lag. The independent variables in this study are auditor reputation and auditor industry specialization. In addition, this study uses the audit committee as a moderating variable. The study population consists of manufacturing companies listed on the Indonesian stock exchange in 2019 and 2020. The data was analyzed using descriptive statistical analysis and regression analysis with the SPSS 25 program. The findings show that, auditor reputation and auditor industry specialization have a significant impact on audit report lag. This research also shows that audit committees can moderate the relationship between auditor reputation and audit report lag, but it does not prove that audit committees can moderate the relationship between auditor industry specialization and audit report lag.